PENGGUNAAN MEDIA MARIONETTES DALAM KEMAMPUAN MENYIMAK USIA 5-6 TAHUN TK NURUL IMAN PEKANBARU - Putri Clawson; Riska Noprianti (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2019)
This study aims to determine the optimization of the use of rope puppet media (Marionettes) in stimulating the ability to listen to the age of 5-6 years at Nurul faith in Pekanbaru City. This study uses qualitative research with a descriptive study approach. This research is located in Nurul Iman Kindergarten, Pekanbaru City. The subjects of this study were class teachers and group B children, amounting to 22 children consisting of 9 boys and 13 girls. the use of marionettes media in stimulating the ability to listen to children aged 5-6 years in kindergarten Nurul Iman Pekanbaru City has been said to be optimal and can improve the ability to listen to children in kindergarten Nurul Iman Pekanbaru City. This is seen from the child's ability to receive and understand what is heard, the child is able to distinguish between sounds and sounds, the child's ability to remember sentences to be heard and repeat them, the child's ability to connect observed objects with the experiences, ideas and feelings and abilities of children in recognizing and expressing rhythmic words.